Comparison between swimming VO2peak and VO2max at different time intervals - Sousa, A.; Figueiredo, P.; Oliveira, N.; Oliveira, J.; Keskinen, K. L.; Vilas-Boas, J. P.; Fernandes, R. J. (The Open Sports Sciences Journal, 2010)
Accepting that the evaluation of the aerobic energy system contribution is very important for swimming training diagnostics purposes and that oxygen uptake kinetics (VO2) is one of the most used parameters in that task, we purposed to assess the variability of the peak VO2 and VO2max values obtained in a 200 m front crawl effort, using five different presentation intervals: breath-by-breath and average of 5, 10, 15, and 20 s. Ten male high-level swimmers performed a 200 m front crawl effort at maximal velocity being attached to a respiratory valve that allowed to directly measure the breath-by-breath VO2 kinetics. VO2 peak was accepted as the highest single value on breath-by-breath sampling and VO2max was considered as the average values of the 5, 10, 15 and 20 s sampling obtained during the test. The obtained VO2peak and VO2max mean values in breath-by-breath and averaged 5 s sampling were similar to those described in the literature for experienced male competitive swimmers. Higher VO2 values were observed for breath-by-breath sampling, being observed differences between that data acquisition method and all the other time intervals (5, 10, 15 and 20 s). Differences were also visible between the 5 s averaging and the other less frequent data acquisitions considered (10, 15 and 20 s), evidencing that less frequent sampling frequencies underestimate the VO2max values. More future research about this topic, also conducted in real competition conditions, i.e., in swimming-pool (not in running or cycle ergometers) is needed.